2016
DOI: 10.1038/srep28446
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing and in silico analyses identify MYB-regulated gene networks and signaling pathways in pancreatic cancer

Abstract: We have recently demonstrated that the transcription factor MYB can modulate several cancer-associated phenotypes in pancreatic cancer. In order to understand the molecular basis of these MYB-associated changes, we conducted deep-sequencing of transcriptome of MYB-overexpressing and -silenced pancreatic cancer cells, followed by in silico pathway analysis. We identified significant modulation of 774 genes upon MYB-silencing (p < 0.05) that were assigned to 25 gene networks by in silico analysis. Further analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Genome-wide studies have identified numerous genes as targets of c-Myb 37,38 ; therefore, the importance of c-Myb in development, cell survival, proliferation, and homeostasis is unequivocal 7 . However, it is not yet clear what type of transcriptional regulation is lost as a critical event resulting from c-Myb reduction during progenitor differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide studies have identified numerous genes as targets of c-Myb 37,38 ; therefore, the importance of c-Myb in development, cell survival, proliferation, and homeostasis is unequivocal 7 . However, it is not yet clear what type of transcriptional regulation is lost as a critical event resulting from c-Myb reduction during progenitor differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of c-MYB correlated with higher grade ovarian cancer which suggested a direct relationship between c-MYB expression and aggressive ovarian cancer. The oncogenic role of c-MYB is not limited to ovarian cancer and has been reported in hematological malignancies as well as several solid tumors [9][10][11][12][13] , Despite such wealth of information regarding the oncogenic potential of c-MYB, its role in cisplatin resistance was not known prior to this report 9 . The study reported a connection between c-MYB expression and acquired cisplatin resistance, but there is still no clear understanding regarding how c-MYB can influence cisplatin resistance.…”
Section: Regulation Of Myb Mediated Cisplatin Resistance Of Ovarian Cmentioning
confidence: 95%
“…IL-6 levels can be reduced by EGCG in breast cancer TME, as part of regulation of tumor-associated macrophages (TAMs) [ 114 ], and IL-18 can be inhibited by resveratrol in melanoma TME, leading to reduced metastasis [ 115 ]. Also, plumbagin has been demonstrated to inhibit the activity of c-MYB [ 116 ], an important modulator of tumor-stromal cross-talk and pancreatic cancer signaling [ 117 ]. In addition, EGCG has been shown to inhibit prostate cancer-associated myofibroblast differentiation [ 118 ].…”
Section: Modulation Of Tumor Microenvironmentmentioning
confidence: 99%